2006
DOI: 10.1002/gps.1683
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes to ageing questionnaire (AAQ): development and psychometric properties

Abstract: The AAQ provides researchers, clinicians and policy makers with a unique scale to measure the impact of successful ageing interventions. It also provides a vehicle for the measurement of how individuals age across cultures and under different economic, political and social circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
347
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(360 citation statements)
references
References 9 publications
11
347
2
Order By: Relevance
“…Evidence of marginal fit or the lack thereof is not unique to the present study and has also been reported among Swiss (Von Steinbuchel et al 2006) and Chinese (Hwang et al 2003) older adults, the latter of these two reporting different suggested modifications than those observed in the present study. Cultural differences serve as a reminder that older people alone possess intimate knowledge of adaptation to the ageing process and their QoL (Laidlaw et al 2007). Further comparative studies of the BREF among older people living in different countries would add to our existing knowledge of the meaning of QoL in the third age and further invite us to embrace its complexities.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of marginal fit or the lack thereof is not unique to the present study and has also been reported among Swiss (Von Steinbuchel et al 2006) and Chinese (Hwang et al 2003) older adults, the latter of these two reporting different suggested modifications than those observed in the present study. Cultural differences serve as a reminder that older people alone possess intimate knowledge of adaptation to the ageing process and their QoL (Laidlaw et al 2007). Further comparative studies of the BREF among older people living in different countries would add to our existing knowledge of the meaning of QoL in the third age and further invite us to embrace its complexities.…”
Section: Discussionmentioning
confidence: 99%
“…Scores on this factor - which we labelled “physical and psychological loss” - were strongly associated with risk of becoming physically frail or pre-frail, but they represent just 1 potential domain of attitudes to ageing. Some other measures for assessing attitudes to ageing include subscales on several domains [29,30]. Another limitation is that due to attrition our analyses were based on 52% of the participants assessed at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Our principal results referred to three dimensions of ageing described by Laidlow (24) and strived to understand which factors of older adults life contributed to each of the dimensions (research question 2). We also intended to describe what seniors meant by expressing positive or negative attitudes to ageing (research question 1).…”
Section: Fig 3 Comparison Of the Staff And The Seniors Living In Inmentioning
confidence: 99%